Transformation of deep‐water methane bubbles into hydrate. Issue 4 (29th July 2014) - Egorov, Alexander V.; Nigmatulin, Robert I.; Rozhkov, Aleksey N.
Abstract This study focuses on the mechanics of methane bubble phase behavior in the gas hydrate stability zone. The transformation of deep‐water methane bubbles into solid hydrate was investigated in Lake Baikal in situ. After being released from the lake bottom, methane bubbles were caught by different traps with transparent walls. When bubbles entered the internal spaces of the traps, the bubbles could be transformed into two different solid hydrate structures depending on the ambient conditions. The first structure was hydrate granular matter consisting of solid fragments with sizes on the order of 1 mm. The second structure was a highly porous solid foam consisting of solid bubbles with sizes on the order of 5 mm. The granular matter did not change as it was brought up to the top border of the gas hydrate stability zone, whereas in the solid foam, free methane rapidly exsolved from the sample during depressurization. We conclude that the decrease in depth and the decrease in the bubble flux rate were key factors in the formation of the hydrate granular matter, whereas the increase in the depth of bubble sampling and the increase in the bubble flux rate facilitated the conversion of bubbles into a highly porous solid hydrate foam.